Autism and the Edges of the Known World: Sensitivities, Language and Constructed Reality - Peeters, Theo; Hubert, Kazik; Bogdashina, Olga (Jessica Kingsley Publishers, 2011)
In this intelligent and incisive book, Olga Bogdashina explores old and new theories of sensory perception and communication in autism. Drawing on linguistics, philosophy, neuroscience, psychology, anthropology and quantum mechanics, she looks at how the nature of the senses inform an individual's view of the world, and how language both reflects and constructs that view. Examining the 'whys' and 'hows' of the senses, and the role of language, Olga Bogdashina challenges common perceptions of what it means to be 'normal' and 'abnormal'. In doing so she shows that autism can help to illuminate our understanding of what it means to be human, and of how we develop faculties that shape our cognition, language, and behaviour. In the final chapter, she explores phenomena often associated with the paranormal - including premonitions, telepathy and déjà vu - and shows that these can largely be explained in natural terms. This book will appeal to anyone with a personal or professional interest in autism, including students and researchers, clinical practitioners, individuals on the autism spectrum and their families, teachers, speech and occupational therapists, and other professionals.